Ascorbate and glutathione independently alleviate arsenate toxicity in brinjal but both require endogenous nitric oxide. Issue 1 (5th May 2021) - Alamri, Saud; Kushwaha, Bishwajit Kumar; Singh, Vijay Pratap; Siddiqui, Manzer H.; Al‐Amri, Abdullah A.; Alsubaie, Qasi D.; Ali, Hayssam M.
Abstract: In this study, we have explored the possible role of ascorbic acid (ASC) and glutathione (GSH) in alleviating arsenate (As V ) toxicity in brinjal roots. Moreover, we have also focused our attention on the possible involvement of endogenous nitric oxide (NO) in accomplishing this task. As V treatment negatively impacts the length and fresh weight of roots and shoots as well as the dry weight and fitness of roots, and this was accompanied by greater As accumulation in roots and shoots of brinjal. As V treatment also declined the endogenous NO level by inhibiting Nitric Oxide Synthase‐like (NOS‐like) activity. Furthermore, As V stimulated oxidative stress markers, caused protein damage by their carbonylation due to downregulation in antioxidants [particularly ascorbate (AsA)‐GSH cycle], leading to disturbed cellular redox status. This, collectively, led to root cell death in brinjal. However, the addition of either ASC or GSH rescued brinjal roots from the toxic effects of As V in. Interestingly, lycorine (an inhibitor of ASC biosynthesis) further increased As V toxicity, while ASC rescued its effects. Moreover, buthionine sulphoximine (BSO, an inhibitor of GSH biosynthesis) interestingly increased further As V toxicity, while GSH rescued the plant from the As toxic effects. An interesting notion of this study was that GSH rescued the toxic effect of lycorine, while ASC rescued the toxic effect of BSO, though the As V toxicity mediated by either ASC or GSH was always accompanied by high endogenous NO level and NOS‐like activity. All together, these results suggest that ASC and GSH independently mitigate As V toxicity in brinjal roots, but both might be dependent on endogenous NO for accomplishing the As V toxicity alleviatory tasks.